Synthesis of Magnesia–Hercynite-Based Refractories from Mill Scale and Secondary Aluminum Dross: Implication for Recycling Metallurgical Wastes - Praphaphan Wongsawan; Nantiya Boonlom; Muenfahn Vantar; Somyote Kongkarat (Ceramics)
This study investigates the synthesis of magnesia–hercynite-based refractories using blends of magnesia powder, aluminum dross (AD), mill scale (MS), and graphite, focusing on the effects of carbon concentration and heating temperature. The results demonstrate successful synthesis at 1550 °C and 1650 °C, with high magnesia content (C80 and D80) leading to the formation of distinct phases, including MgO, FeAl2O4, MgFeAlO4, CaMg(SiO4), and Ca3Mg(SiO4)2, which influence the ceramic’s microstructure and mechanical properties. Increased magnesia content reduces porosity and enhances crushing strength, while heating to 1650 °C significantly improves densification and nearly doubles cold crushing strength, from 43.77–58.97 MPa at 1550 °C to 76.79–95.67 MPa at 1650 °C. These findings suggest that the synthesized refractories exhibit properties comparable to commercial magnesia–hercynite bricks, with potential for the further development for industrial rotary kiln applications.